Genome- and transcriptome-wide association studies provide insights into the genetic basis of natural variation of seed oil content in Brassica napus - Tang, Shan (2021)
Seed oil content (SOC) is a highly important and complex trait in oil crops. Here, we decipher the genetic basis of natural variation in SOC of Brassica napus by genome- and transcriptome-wide association studies using 505 inbred lines. We mapped reliable quantitative trait loci (QTLs) that control SOC in eight environments, evaluated the effect of each QTL on SOC, and analyzed selection in QTL regions during breeding. Six-hundred and ninety-two genes and four gene modules significantly associated with SOC were identified by analyzing population transcriptomes from seeds. A gene prioritization framework, POCKET (prioritizing the candidate genes by incorporating information on knowledge-based gene sets, effects of variants, genome-wide association studies, and transcriptome-wide association studies), was implemented to determine the causal genes in the QTL regions based on multi-omic datasets. A pair of homologous genes, BnPMT6s, in two QTLs were identified and experimentally demonstrated to negatively regulate SOC. This study provides rich genetic resources for improving SOC and valuable insights toward understanding the complex machinery that directs oil accumulation in the seeds of B. napus and other oil crops.